Reverse-Flow Intrinsic Fasciocutaneous Island Flaps in Foot Reconstruction. (December 2017) - Bahk, Sujin; Doh, GyeongHyeon; Hong, Ki Yong; Lim, SooA; Eo, SuRak
Reconstruction of soft tissue defects in the foot remains a challenge due to its specialized tissue for weightbearing and ambulation. Considering the principle of replacing "like with like, " adjacent soft tissues would be a best option for a donor site. Although several kinds of reverse-flow island flaps for the lower leg have been well described, intrinsic foot reverse flow flaps have been rarely reported. We describe 3 kinds of reverse-flow intrinsic fasciocutaneous flaps (RIFFs) for foot reconstruction. From September 2012 to August 2015, a retrospective study was done on case notes of all patients who had a RIFF for coverage of soft tissue defects within the foot following trauma or tumor ablation. A total of 7 patients were included in this study, with an average of 5 × 3.5 cm sized defects in the forefoot, second and third web space, and sole, which were reconstructed with RIFF. All flaps were well perfused and recovered excellent function of the foot with satisfactory aesthetics and minimal limitations in range of motion. However, one case showed a complication of venous congestion, due to remnant scar tissues, which resolved after medical leech application. Donor defects healed completely with split thickness skin grafting in all cases. Soft tissue defects within the foot were repaired successfully by RIFF. In spite of its technical challenges, it is a reliable one-stage procedure requiring no microsurgical anastomosis. Precise vascular evaluation of the reverse inflow has to be preceded for satisfactory outcome of RIFF.